2008
DOI: 10.1128/jvi.02154-07
|View full text |Cite
|
Sign up to set email alerts
|

Electron Cryomicroscopy Reveals Different F1+F2 Protein States in Intact Parainfluenza Virions

Abstract: Electron cryomicrographs of intact parainfluenza virus 5 (PIV5) virions revealed two different surface structures, namely, a continuous layer and distinct individual spikes. The structure of these spikes reconstructed from intact virions was compared with known F ectodomain structures and was found to be different from the prefusion PIV5 F0 structure but, surprisingly, very similar to the human PIV3 F postfusion structure. Hence, we conclude that the individual F1؉F2 spikes in intact PIV5 virions also correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…We also have found that, in the absence of HN, processed F is sensitive to proteolysis (18). Taken together, these data suggest that HN protects processed F from untimely activation (18,37), and only when it is receptor engaged does it proceed to activate F.…”
Section: Discussionsupporting
confidence: 52%
“…We also have found that, in the absence of HN, processed F is sensitive to proteolysis (18). Taken together, these data suggest that HN protects processed F from untimely activation (18,37), and only when it is receptor engaged does it proceed to activate F.…”
Section: Discussionsupporting
confidence: 52%
“…Figure 3B indicates that in the period just around the time of fusion, a connector between the virus and cell is made and there is preparation for moving the RNP. The spikes are drawn differently because the viral glycoproteins undergo a conformational change during the fusion process (36,56), and some of the early electron microscopy studies reported changes or loss of defined spikes during fusion (27,29).…”
Section: Membrane Uncoating Of Paramyxovirusesmentioning
confidence: 99%
“…Unfortunately, these images lack the resolution for an identification of the molecular nature of the spikes (attachment or F protein) or the distinguishing between densely packaged H and F head domains of different heights and laterally aligned head domains. Indeed, a recent single-particle reconstruction based on cryo-electron microscopy images of HPIV5 particles revealed that defined spikes correspond to F in a postfusion conformation, which was interpreted as a product of possible premature F refolding (38). These two-dimensional images of heavy-metal-stained particles did not reveal F spikes in a prefusion conformation.…”
mentioning
confidence: 99%
“…These two-dimensional images of heavy-metal-stained particles did not reveal F spikes in a prefusion conformation. Rather, a dense surface layer was considered to correspond to prefusion glycoprotein hetero-oligomers (38). In addition to further-advanced image reconstructions, biochemical assessment of alternative docking modes is imperative for the elucidation of the organization of functional fusion complexes of paramyxovirinae.…”
mentioning
confidence: 99%